Turning up the heat : an analysis of the historic, scientific and socio-political complexities influencing climate change reporting in the modern newsroom - Joubert, Leonie (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Journalism))--University of Stellenbosch, 2006.